Comparative Study of the Antibiotic Potency of Natural (Cyanthillium cinereum and Moringa oleifera) and Synthetic (Ampicillin and Erythromycin) Antibiotics - Headley, Tresonne; Daniel, Ruth; Liverpool, Elford; Ansari, Abdullah Adil (Journal of pure & applied microbiology : an international research journal of microbiology, 2020)
The aim of this study was to compare the antibiotic potency of Cyanthillium cinereum and Moringa oleifera (natural antibiotics) against Ampicillin and Erythromycin (synthetic antibiotics) using zone of inhibition and both the natural and synthetic antibiotic was treated against Staphylococcus aureus, Klebsiella. pneumoniae and Pseudomonas aeruginosa. The extracts from the natural agents were obtained by the use of methanol (polar) and hexane (non-polar). The bacteria were treated with six different conc. (100%, 75%, 50%, 25%, 10% and 5%) of the extracts, where the largest zone of inhibition was observed with C. cinereum extract at 5% concentration against S. aureus with mean and standard deviation of 22.1±2.1. S. aureus followed by P. aeruginosa was most susceptible towards the treatments. The correlation (Pearson) indicated that the conc. of the extract was indirectly proportional to the zone of inhibition. The phytochemical analysis revealed that C. cinereum contained alkaloids, catecholic tannins, saponins, flavones, volatile oils phenols and steroids and M. oleifera only contained Alkaloid, tannins and steroids.